GLOBAL EXPERIENCE OF USING HORSES FOR THE REHABILITATION OF MILITARY PERSONNEL - Гончаренко, Ігор; Погрібна, Анна (SWorldJournal, 2025)
This article is devoted to the study and analysis of the application of hippotherapy in the comprehensive rehabilitation of military personnel. Hippotherapy, also known as therapeutic horseback riding, is increasingly recognized as an effective method for